Chemical composition, fatty acid profile, antioxidant content, and microbiological loads of lesser mealworm, mealworm, and superworm larvae - Simona Mattioli; Filippo Fratini; Chiara Cacchiarelli; Valentina Martinis; Tiziano Tuccinardi; Gisella Paci; Alessandro Dal Bosco; Simone Mancini (Italian Journal of Animal Science, 2024)
In the last decade, great attention was placed on insects to increase feed-food production without negatively affecting the environment. In this research study we compare three different insect species (Alphitobius diaperinus, Tenebrio molitor, and Zophobas morio - lesser mealworm, mealworm, and superworm), fed the same substrate, on the chemical composition, fatty acid (FA) profile, antioxidant content, and microbiological loads. Superworm larvae show higher dry matter (38.06%) and ether extract (17.65%) contents followed by mealworm and lesser mealworm larvae (32.77%, 27.11% and 13.86%, 10.78%, respectively). No differences were detected in the crude protein and ash content. Superworm larvae showed the highest content of SFA (41.43% vs 39.16% and 28.52% of total FA, in lesser mealworm and mealworm, respectively), while mealworm larvae were the richest in MUFA (40.61% vs 34.38% and 32.98% of total FA, in super and lesser mealworm, respectively) and PUFA (29.05% vs 22.29% and 21.21% of total FA in super and lesser mealworm, respectively). Anyhow, in all the larvae the three more representative fatty acids were oleic acid, linoleic acid, and palmitic acid. The least beneficial ratio of n-6/n-3 was detected in Alphitobius diaperinus larvae (53.84), while Zophobas morio larvae showed the healthier ratio (16.04). The antioxidant contents determination revealed a linkage to the fatty acids content. Low differences were determined in microbiological loads of the larvae. The characteristics of the insects revealed the great potential of these three species highlighting the capacities to respond to different requests derived from the food and feed sectors.Highlights Superworm larvae showed the highest content of SFA Mealworms larvae were the richest in PUFA The fat-soluble vitamin content followed the fatty acids content